(untitled) (Third Sector Social Economic Review, 2023)
Technological advancements significantly impact business and marketing. Online customer reviews, along with customer complaints, are concepts arising as a result of technological developments. Improving e-commerce has created a new channel through which customers can express their satisfaction and complaints. The reviews section, available on nearly all e-commerce platforms, enables customers to share their experiences. Reviews are voluntarily created only after customers have made a purchase, making reviews trustworthy and valuable data. The research is significant for e-commerce businesses to recognize variables related to dissatisfaction in customer relationship management. Identifying the sources of complaints and customer expectations is crucial for enhancing both the product and communication processes, enabling businesses to improve their marketing strategies. In the research, 6714 customer complaints were obtained through web scraping method. The acquired data underwent content analysis. The data was coded, revealing four categories: product material, packaging, size, and cargo. Remarkably, product material accounted for 69.33% of all complaints, approximately half of which exhibited different levels of negative expressions. It was revealed that packaging and cargo are distinct areas of concern for complaints. The research has emphasized that customer feedback reduces research costs for businesses and review management should be an integral part of digital marketing.